1998
DOI: 10.1136/fn.78.1.f3
|View full text |Cite
|
Sign up to set email alerts
|

Nebulisation of surfactants in an animal model of neonatal respiratory distress

Abstract: Aims-To evaluate pulmonary deposition and gas exchange following nebulisation of two surfactants by either a jet or an ultrasonic nebuliser. Method-After bronchoalveolar lavage (BAL), 19 rabbits were ventilated in four groups. Group A1 (n=5) and A2 (n=6) received Technetium-99m labelled Exosurf, and groups B1 (n=4) and B2 (n=4) received radiolabelled Survanta. Groups A1 and B1 received jet nebuliser therapy, whereas groups A2 and B2 received ultrasonic nebuliser. Pulmonary deposition, distribution, and blood g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…Despite many experimental studies of nebulized surfactant, using various animal models of surfactant deficiency or depletion, the results have been inconsistent and often disappointing. In some studies, there was no benefit from nebulized surfactant (10,12,13), whereas in others a significant improvement in gas exchange and lung mechanics was observed (9,11). A possible explanation of these findings is the low rates of surfactant deposition within the lung.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite many experimental studies of nebulized surfactant, using various animal models of surfactant deficiency or depletion, the results have been inconsistent and often disappointing. In some studies, there was no benefit from nebulized surfactant (10,12,13), whereas in others a significant improvement in gas exchange and lung mechanics was observed (9,11). A possible explanation of these findings is the low rates of surfactant deposition within the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Nebulization of surfactant offers an attractive alternative. Unfortunately, studies of nebulized surfactant have shown inconsistent clinical response and surfactant distribution (9)(10)(11)(12)(13)(14)(15)(16). Moreover, most of the studies, even those in which a lung function improvement was observed, reported very low (<10%) fractions of surfactant deposition into the lung (9,12,(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…Multiple studies have reported respiratory improvement with surfactant aerosol in animals with surfactant deficiency or dysfunction, 131,135,153,[155][156][157][158][159][160][161][162][163] although other aerosol studies have been less positive. [164][165][166][167] Several animal studies have directly compared aerosolization to tracheal instillation, and reported that aerosolization can have equal or greater effectiveness, 131,155,159 whereas others have found that instillation is more effective than aerosolization. 131,165,168 An example illustrating the need for further clarity on this issue is the study by Lewis et al 131 In lung-lavaged sheep, exogenous bovine lung extract surfactant was effective when instilled but ineffective when aerosolized, whereas beractant in the same animal model was more effective when aerosolized than when instilled.…”
Section: Animal Studies Of Surfactantmentioning
confidence: 99%
“…Delivery of aerosolized SF (SF-aero) might be a useful alternative to tracheal instillation for the treatment of RDS, but experimental and clinical results with this technique remain inconsistent (6)(7)(8)(9)(10)(11)(12)(13). Discrepancies in the results can be attributed to the use of different animal models of lung injury (neonatal RDS vs. adult RDS), aerosol devices (jet vs. ultrasonic), sites for the placement of the aerosol devices (endotracheal tube vs. nasal prong), and SF preparations (natural vs. synthetic), as well as variations in the doses used.…”
mentioning
confidence: 99%